Behavioral Aspects in the Budget Preparation Process at "X" Hospital - Prayitno, Hadi; Trisnaningsih, Sri (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to determine behavioral aspects in the budget preparation process that occurs at the Undaan Eye Hospital, Surabaya. The research uses a descriptive qualitative method, namely by explaining, describing and comparing the data with existing theories and then analyzing it to obtain a conclusion. Data was obtained by field observation by conducting interviews and documentation. The results of this research indicate that the Undaan Eye Hospital in Surabaya has implemented a participatory work program and budget preparation process using a bottom up model, namely an approach model where each implementing manager is given the freedom to determine activities and work programs. Top management control over behavior in budget preparation and budget implementation has been carried out well with monthly reports and the use of technology and information systems.